The use of podcasts in improving students’ speaking skill - Bustari, Ahmad; Samad, Iskandar Abdul; Achmad, Diana ((JELE) Journal Of English Language and Education, 2017)
AbstractPodcast is a digital recording which contains a recorded programs from television, radio, and interviews. Many researchers have discussed about the podcast as an alternative teaching media to support students developing their speaking skills. This research article aims at finding out if there is a significant improvement on students’ speaking skills by using this Podcast. Class XI IS3 was chosen as the sample of this study with total 30 students. This pre-experimental study employs pre-test and post-test. These tests are provided in the form of oral tests. The data from these tests were then calculated by using statistical formulas. The result showed that the post-test score was higher than the pre-test. The finding showed that there was a significant improvement of the students’ speaking skills performance after undertaking treatments. Thus, podcast media can be used as one of the alternative media in teaching English especially speaking skill in EFL classes.